TINDAK UJAR KOMPETITIF DAN KONFLIKTIF DALAM FILM HACKSAW RIDGE KARYA MEL GIBSON - WANGANIA, SHARON CLAUDIA; KODONG, FENTJE; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research is entitled â€œCompetitive Act and Conflictive Act in the Film Hacksaw Ridge by Mel Gibsonâ€ is described based on pragmatics analyze. This study focuses on competitive and conflictive acts that used in the film Hacksaw Ridge by Mel Gibson. This research aims at identifying and describing the competitive and conflictive acts in the film Hacksaw Ridge. In collecting data, the writer elicits them through the conversation among the characters in the film. To analyze them, the writer used descriptive analysis based on Leechâ€™s theory. Leech divided competitive and conflictive acts into eight kind which is ordering, asking, demanding, threatening, reprimanding, begging, accusing, and cursing. It is expected that study will help student and also readers in learning pragmatics especially the competitive and conflictive acts in the film. Â Â Â Â Â Keywords : Speech act; illocutionary act; competitive and conflictive acts.